056 The differential contribution of nitric oxide and endothelium-derived hyperpolarising factor to resting and stimulated vasodilator tone in healthy black and white individuals. (22nd September 2015) - Ozkor, M A; Murrow, J R; Rahman, A; Kavtaradze, N; Arshad, S; Syed, H; Li, J; Manatunga, A; Quyyumi, A A
Abstract : Whether impaired endothelial function in individuals of black ethnicity compared to whites is due to alterations in nitric oxide (NO) or endothelium-derived hyperpolarizing factor (EDHF) activity is unknown. We hypothesised that there is a differential racial contribution of these two agonists to vasodilator tone. Methods: In 45 white and 36 black healthy subjects, we measured forearm blood flow (FBF) using strain gauge plethysmography at rest and after infusions of bradykinin (BK, 100, 200, 400 ng/min), acetylcholine (ACH 7.5, 15, 30 μg/min) and sodium nitroprusside (1.6 and 3.2 μg/min). Measurements were repeated after NO blockade with L-NMMA, calcium-dependent potassium channel blockade with tetraethylammonium (TEA, inhibiting EDHF activity), and combined blockade. Results: Both L-NMMA and TEA reduced resting FBF in both groups indicating similar contribution of NO and EDHF to resting tone; whites vs blacks with L-NMMA: −22% and −18%, p=0.01; with TEA: −23% and −24%, p=0.001; with L-NMMA+TEA: −42% and −35%, p=0.001, respectively, compared to baseline. BK-mediated vasodilation was greater in whites than blacks (p=0.04). L-NMMA attenuated BK responses in whites (−30%, p=0.0005) but not in blacks (−18%, p=0.11), indicating a greater contribution of NO in whites. TEA reduced blood flow (23% and 22% in whites and blacks, respectively, p<0.001), indicating similar contribution of EDHF in both groups. ACH-mediated vasodilation was greater in whites than blacks (p=0.001). TEA did not change flow in either group, but L-NMMA attenuated ACH-mediated dilation only in whites and not in blacks (−18%, p<0.01 vs −2%, p=NS), indicating a reduced NO in blacks. Sodium nitroprusside-mediated dilation was greater in whites than blacks (p=0.006), indicating reduced sensitivity of the smooth muscle cells to NO in blacks. Conclusions: Although NO and EDHF contribute equally to resting blood flow, there is reduced availability and sensitivity to NO during pharmacologic stimulation even in healthy blacks compared to whites. In contrast, EDHF activity is preserved in blacks. Preserved EDHF but reduced NO activity in blacks may underlie the increased risk of hypertension and cardiovascular disease in black individuals, and may have therapeutic implications that need to be explored.